A burst capacity model for pipelines containing pinhole-in-corrosion defects - Yufei Shen; Wenxing Zhou (Journal of Pipeline Science and Engineering, 2025)
This study develops a practical burst capacity model for oil and gas pipelines containing pinhole-in-corrosion (PIC) defects based on results of extensive parametric three-dimensional finite element analyses (FEA) that are validated by full-scale burst tests of corroded pipe specimens reported in the literature. The PIC defect considered in this study contains a cylindrical-shaped pinhole located inside a cuboidal-shaped general corrosion. The proposed model takes the form of the well-known PCORRC model for the burst capacity of the general corrosion plus a correction term taking into account the impact of the pinhole, whereby the correction term is evaluated as a function of the depth and length of the general corrosion as well as the depth and relative position of the pinhole using the Gaussian process regression based on the results of parametric FEA. The accuracy of the proposed PIC model is demonstrated using 16 FEA cases and shown to be higher than that of the well-known RSTRENG model and a burst capacity model for complex-shaped corrosion defects reported in the recent literature.